A Detailed Comparison of the Performance of the Standard versus the Nijmegen Modification of the Bethesda Assay in Detecting Factor VIII:C Inhibitors in the Haemophilia A Population of Canada - Giles, Alan R.; Verbruggen, Bert; Rivard, Georges E.; Teitel, Jerome; Walker, Irwin; Association of Hemophilia Centre Directors of Canada; Factor VIII/IX Subcommittee of Scientific and Standardization Committee of International Society on Thrombosis and Haemostasis; on behalf of (Thrombosis and Haemostasis, 1998)
The Bethesda assay is widely used to monitor the development and progress of Factor VIII:C inhibitors. Factor VIII stability in the substrate plasma (normal pool) is compromised by pH shift and reduction in protein concentration. Preliminary study, by Verbruggen and colleagues (8), suggested a reduction in spuriously positive assay results may result from buffering the normal pool plasma substrate with imidazole to pH 7.4 and substituting Factor VIII deficient plasma for imidazole buffer in the control incubation mix. These laboratory findings have now been confirmed by the performance of both the standard and the modified Bethesda assays in parallel on 877 patient samples screened during the Factor VIII:C Inhibitor Surveillance Program instituted following the conversion of all Canadian haemophilia A patients to recombinant Factor VIII. Although this study does not address the question of the clinical significance of spurious positive assays, these laboratory findings do support the conclusions of Verbruggen and the modified assay has recently been endorsed by the Factor VIII/IX Subcommittee of the SSC.